Pengaturan Hukum terhadap Hak Kreditur Konkuren yang Dirugikan dalam Rangka Penegakan Hukum yang Transparan dan Berkeadilan - Hermawan, Muhammad Bayu (IBLAM LAW REVIEW, 2025)
In Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, there are still legal restrictions governing the rights of concurrent creditors. There are many conclusions which are the result of the unregulated rights of concurrent creditors which give rise to many new problems. The main objective in a process before the court is to obtain a judge's decision that has permanent legal force, but in bankruptcy cases, concurrent creditors often do not receive certainty and fair legal enforcement. The method used in this research is normative juridical by conducting research through literature on secondary data, especially primary legal materials in the form of statutory regulations and secondary legal materials in articles or journals, using the theory of just legal certainty. The results of research provide insight and direction to fill the legal vacuum in the regulation of concurrent creditor rights by including transparency and input into elements of special institutions that manage and determine bankruptcy assets in Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.